Bibliometric analysis of the 200 most cited papers in the journal Vojnosanitetski pregled - Golubović, Jagoš; Golubović, Sonja (Vojnosanitetski pregled, 2025)
Background/Aim. Vojnosanitetski pregled (VSP) is the official scientific and professional journal of the University of Defence in Belgrade, Serbia. VSP is a peer-reviewed journal that publishes a wide range of scientific and professional articles. The aim of the study was to perform a bibliometric analysis of the 200 most cited articles published in VSP, and to as-sess the impact, significance, and scientific contribution of the journal. Methods. Using the Web of Science (WoS) Core Collection (WoSCC) database, 2,664 articles published from 2008 to December 31, 2022, were analyzed, focusing on citation counts, author productivity, and collaboration networks. Results. The analysis revealed that the majority of the most cited articles came from Serbian institutions, with the University of Belgrade being the most prolific contributor. The top five most cited authors as well as the most cited article were identified, and a trend of increasing significance of research on bioactive compounds was noticed. The study also observed a shift in key word usage over time, reflecting changes in research trends within the journal. The collaboration network analysis showed a strong clustering among the leading authors, indicating a collaborative culture that contributes to the journal’s influence. Conclusion. Emphasizing the importance of targeted collaborations makes it evident that maintaining and expanding the journal’s impact on the scientific community is the key to improving medical research. Despite limitations such as reliance on a single database, the findings provide valuable insights into the journal’s role in advancing medical research and highlight the importance of targeted collaboration.
Keywords: bibliometrics; interdisciplinary communication; journal impact factor; research.